A novel methodology to realistically monitor office occupant reactions and environmental conditions using a living lab. (15th February 2018) - Jamrozik, Anja; Ramos, Christian; Zhao, Jie; Bernau, Joleen; Clements, Nicholas; Vetting Wolf, Tracee; Bauer, Brent
Abstract: Indoor environmental conditions, including acoustic, lighting, and thermal conditions, can impact the experience of occupants. How should these conditions be combined to optimize indoor environments for occupants? Living labs, in which study participants occupy a simulated real-world environment for an extended period, offer a new way to test the interactive effects of environmental conditions. In a proof-of-concept study, we tested whether varying combinations of environmental conditions in a simulated open-office environment would affect the experience of its occupants. Six different environmental "scenes"–combinations of acoustic, lighting, and thermal conditions—were varied weekly over 18 weeks. One scene had environmental conditions commonly found in offices, including participants' previous office, and served as the baseline against which the other scenes were compared. We tested the effects of office environmental conditions on occupants' satisfaction and workday experience in the environment. Further, we tested whether the influence of the environment would extend outside of the time spent at work to affect occupants' feelings and health behaviors. Changes in office environmental conditions affected occupants' environmental satisfaction and their workday experience. Outside of the office, environmental conditions affected people's feelings (e.g., happiness) and health behaviors (reported sleep problems). These findings demonstrate that living labs offer a powerful methodology to test the interactive effects of environmental conditions on occupants' experience, both inside and outside the lab. Highlights: Experiment tested effect of environment on occupants of an open office in living lab. Six combinations of acoustic, lighting, and thermal conditions varied over 18 weeks. Satisfaction, workday experience, feelings, and health behaviors were measured. The office environment affected occupants' experience inside and outside the space. Living labs offer viable method to test the interaction of environmental conditions.